Pengaruh variasi waktu dan suhu pirolisis terhadap kualitas bio-oil dari limbah biomassa plant filter aid (Lignoselulosa D07) - Usman, Nur Wahidah; Suryanto, Suryanto; Kalla, Ruslan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
In line with the increase in world population and technological developments, the need for energy continues to increase while energy source reserves are decreasing. More than 80% of the supply of energy sources comes from fossil fuels including coal, petroleum, and natural gas. The solution to the need for energy from fossil raw materials is the use of alternative energy sources, one of which is biomass. Biomass Waste of Plant Filter Aid (Lignocellulose D07) is one of the biomass by-products in one of the grass processing industries that comes from plant lignocellulose. The quality of biomass can be improved by using the pyrolysis method. Pyrolysis is a thermal degradation method without oxygen. Pyrolysis produces two main products, namely char (charcoal) and liquid smoke (Bio-oil). Bio-oil obtained from the pyrolysis process can be used as fuel and preservative. The quality of bio-oil from the pyrolysis process is influenced by several factors including the influence of time and temperature. Based on these influences, this study will aim to determine the effect of time and temperature on the quality of bio-oil. The pyrolysis time used in this study was 1 hour, 2 hours and 2.5 hours, while the temperature used in this study was 300oC, 350oC and 400oC. Based on the research results obtained, the best time and temperature from this research data were 2.5 hours and 400oC with the largest yield of 57%. Pyrolysis time and temperature not only affect the yield but also affect the pH, density and content of bio-oil. From the research data, the effect of pyrolysis time and temperature on the pH value is that the higher the time and temperature, the lower the pH value produced, the more acidic the bio-oil. Meanwhile, the bio-oil content obtained from the results of GC-MS analysis is dominated by acid compounds (acetic acid). The acetic acid content combined with hydrogen can produce ethanol.